EMPIRICAL LINKAGES BETWEEN EDUCATION, POVERTY, AND ECONOMIC GROWTH: NEW EVIDENCE FROM THE GROWTH EMPIRICS OF PAKISTAN - Shaheen, Ruqia; Yasmeen, Najma; Iqbal, Sidra; Masood, Sadia (The journal of contemporary issues in business and government, 2021)
Income poverty is defined as the lack of necessities for minimum material wellbeing determined by the national poverty line. Human Poverty means the denial of choices and opportunities for a life in all economic and social aspects.For this purpose, Secondary data is used to analyze the linkages between Education,Poverty, and economic growth. The study used data from different sources for the period of 1976 to 2020. ARDL was applied for the analysis. Econometric analysis is carried out to analyze the connection between the core variables of the study. The conclusion is of the view that poverty must be reduced for the engravened of economic growth. The industrial sector positively impacts economic growth Data on these variables is collected from different sources.It is recommended that the government and other policymakers focus on resolvingpoverty and unemployment in Pakistan.Government should make different policies to reduce poverty.Poverty reduction and education enhancing policies should be adopted for the development of the economic growth of the country.